Nested variant of urothelial carcinoma of the urinary bladder - Tadashi Terada (Rare Tumors, 2011)
The nested variant of urothelial carcinoma (NVUC) is characterized by the presence of benign-appearing urothelial carcinoma cells in the lamina propria, sparing the surface urothelial involvement. NVUC shows aggressive clinical course despite of benign-looking histology. Herein reported are two cases of NVUC. One is 80-year-old woman, and another is 78-year-old man. In both cases, atypical cells forming nests and tubules were seen in the lamina propria without surface urothelial involvement. One case resembled nephrogenic metaplasia and another proliferated Brunn’s nest or inverted papilloma. Immuno - histochemically, both cases showed positive p53 and high Ki67 labeling, suggesting that both cases are malignant. Immuno histo - chemically, one case was characterized by positive cytokeratins, EMA, p53, Ki-67 (labeling= 15%), α-methylacyl CoA racemase, CA19- 9, and MUC1, and another case by positive cytokeratins, EMA, p63, p53, Ki-67 (lebeling= 30%), CD10, CEA, and MUC1. Cyto keratin immunoprofiles were described and other antigens’ expressions were shown. The patients are now free of tumor 6 and 15 months after the resection of the bladder tumor.